APPLICATION OF GEOPHYSICAL METHODS TO THE STUDY OF THE MECHANISM OF SPRINGS - Vargemezis, G.; Tsourlos, P.; Stamoulis, K. (Bulletin of the Geological Society of Greece, 2007)
The application of geophysical investigation to the study of the mechanism of a spring system is discussed. The springs are located within the Southern minefield of the Power Public Corporation in Ptolemais (Greece) in a small valley which is supposed to be filled with the excavation products of the mine. Thus, the aim is to protect the stability of the future valley fill from the water circulation at its floor. The scope of the survey is to study the mechanism of the spring in order to pump the underground water and minimize the water supply of the main source. A number of wells have been constructed along a line that was considered to cross the path of the underground water in order to pump the water but they failed. Geophysical investigation has been decided in order to contribute to the solution of the problem. Electrical tomographies have been conducted in an effort to detect the underground path where the underground water flows towards the springs. The results of the application of geoelectrical tomography and VLF methods showed a faulting system where the underground water is flowing and finally forms the springs.